2017
DOI: 10.1186/s40834-017-0043-8
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of a mobile phone-based intervention to support post-abortion contraception in Cambodia

Abstract: BackgroundThe MObile Technology for Improved Family Planning (MOTIF) trial assessed a mobile phone-based intervention comprising voice messages and counsellor support to increase post-abortion contraception at four Marie Stopes International clinics in Cambodia. The aim of this process evaluation was to assess participants’ interaction with the intervention from a service provider perspective.Methods(1) We conducted a descriptive analysis to assess participants’ interaction with the intervention. (2) In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…Our previous analysis found that the proportion of women that requested to speak to a counsellor (pressing ‘1’) decreased from message one to six [12], which is consistent with reports from the interviews that health issues often resolved over time.…”
Section: Discussionsupporting
confidence: 79%
“…Our previous analysis found that the proportion of women that requested to speak to a counsellor (pressing ‘1’) decreased from message one to six [12], which is consistent with reports from the interviews that health issues often resolved over time.…”
Section: Discussionsupporting
confidence: 79%
“…The intervention comprised automated interactive voice messages sent to women's mobile phones in the 4 months after MR. The Cambodia intervention relied heavily on call center counseling, and the cost of this component has been cited as a possible barrier to scale-up 43 . We explored whether an intervention containing more detailed automated content about contraception could be effective.…”
Section: Introductionmentioning
confidence: 99%
“…Between October 2011 and August 2012, a total of 25,236 pregnant women were recruited into the study (13,332 in the intervention arm and 11,904 in the placebo arm). Of these, 13,937 (55.2%) completed the follow up and included in the final analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Attempts have also been made to use mobile phone text messaging to address issues related to maternal and child health including interventions to support post-abortion contraception (13), infertility treatment (14), lactation management (15), and infant feeding (16). While the overarching goal of mobile phone text messaging seeks to promote behavioural changes in both health care providers and the target population of interest, text messaging intervention evaluated to date have met with varying degrees of success (11,12).…”
Section: Introductionmentioning
confidence: 99%